Two new species and a new country record of Pselaphitae (Coleoptera: Staphylinidae: Pselaphinae) from the Nanling Mountains, China - Zhang, Yong-Qin; Yin, Zi-Wei (Zootaxa, 2024)
The Pselaphitae fauna of the Nanling Mountains is sporadically documented. In this paper, two new species of the tribe Tyrini are described and characterized: Linan maoermontis sp. nov. (Guangxi), and Pselaphodes nanlingensis sp. nov. (Guangdong). Poroderus longicornis Raffray (type locality: Laos) is newly recorded from China (Jiangxi). Illustrations of the habitus and taxonomically informative characters of these three species are provided to aid in their identification.